Clinical evaluation and comparison of the Infrasonde, Arteriosonde, and mercury sphygmomanometer in measurement of blood pressure in children. - Savage, J M (1979)
Both systolic and diastolic pressures can be measured in children with the mercury sphygmomanometer, the Arteriosonde and the Infrasonde. Estimates made blindly with these instruments were compared with directly measured intra-arterial blood pressures in 50 children aged between 4 days and 14 years. Systolic and diastolic estimates with the three techniques showed highly significant correlations with simultaneous intra-arterial measurements (P less than 0.001). The Infrasonde diastolic estimates were least satisfactory and the slope of the regression line against the intra-arterial pressure differed significantly from unity (y=0.54x+29.53). In 11 small children a satisfactory diastolic estimate could not be obtained with the mercury sphygmomanometer. While the mercury sphygmomanometer should remain the standard hospital equipment, an Arteriosonde would be valuable if it is difficult to hear Korotkoff's sounds on auscultation and if a diastolic pressure is required. For research investigations into childhood blood pressure an Arteriosonde or mercury sphygmomanometer, coupled with a device to exclude observer bias, is probably most suitable. Although the Infrasonde is not sufficiently accurate for research purposes, it is acceptable for routine ward use.